High performance hierarchical torus network under adverse traffic patterns - Rahman, M.M. Hafizur; Sato, Yukinori; Inoguchi, Yasushi (Academy Publisher, 2012)
A Hierarchical Torus Network (HTN) is a 2D-torus network of multiple basic modules, in which the basic modules are 3D-torus networks that are hierarchically interconnected for higher level networks. The dynamic communication performance of the HTN using the dimension-order routing under common traffic patterns have been evaluated, and have been shown to be good. However, dynamic communication performance of HTN under adverse traffic patterns has not been evaluated yet. In this paper, we evaluate the dynamic communication performance of HTN using a deadlock-free dimension order routing with 3 virtual channels under adverse traffic patterns, and compare it with H3D-mesh, mesh, and torus networks. It is shown that even under adverse traffic patterns, the HTN yields high throughput and low average transfer time, which provide better dynamic communication performance than H3D-mesh, mesh, and torus networks.